Graphene-oxide doped 2.9.16.23-tetrakis-4-{4-[(2E)-3-(naphthalen-1-yl)prop-2-enoyl]phenoxy}-phthalocyaninato cobalt(II)/Au photodiodes - Ocaya, R. O.; Dere, A.; Tuncer, H.; Al-Ghamdi, Ahmed A.; Sari, Derya C.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
The device parameters of Al/GO:CoPc/p-Si/Au Schottky diodes were investigated using direct current-voltage (I-V), photocurrent and impedance spectroscopy. The ideality factor of the diode was found to depend significantly on GO content. The calculated barrier heights had low variance over the range of illumination intensities per doping level and averaged 0.575 for the undoped diode, and 0.769 +/- 0.001 eV taking all the diodes having GO content. Capacitance-voltage (C-V) measurements show that the capacitance decreases with increasing frequency, suggesting a continuous distribution of interface states over the surveyed 100 kHz-1 MHz frequency range. The photocurrent characterizations show that the photocurrent increases with illumination intensity suggesting that the devices are suitable for photosensor applications. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Graphene oxide; Cobalt phthalocyanine; Photodiode